Orientation method and application of cyanobiphenyl liquid crystal doped with organic donor material
By doping organic small molecule donor materials in cyanobiphenyl liquid crystals and utilizing surface energy differences for directional assembly, combined with adjusting the surface tension of the solvent, the problem of difficult control of the microstructure of cyanobiphenyl liquid crystals is solved, and high conductivity is achieved The uniform orientation of the properties and large area improves the performance and application range of LCD optoelectronic devices.
Patent Information
- Application Number
- CN202411387469.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-03
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-03
AI Technical Summary
In the prior art, the microstructure of cyanobiphenyl liquid crystal is difficult to control and it is difficult to form a large area uniform orientation, which limits its conductivity and application range.
Direction-induced assembly is performed by doping organic small molecule donor materials in cyanobiphenyl liquid crystals and forming an oriented composite by using the large surface energy difference between the superhydrophobic structured shaped substrate and the superhoriphilic whole substrate. structure. At the same time, the surface tension of the solvent is adjusted to optimize the orientation and electrical properties of the composite.
The uniform orientation and high conductivity of cyanobiphenyl liquid crystal are achieved, the performance and application range of liquid crystal optoelectronic devices are improved, and the preparation method is simple and cost-effective.
Smart Images

Figure CN119493307A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of liquid crystal materials and charge transport, and in particular to an orientation method of cyanobiphenyl liquid crystal doped with an organic small molecule donor material and its application. Background Art
[0002] As a prominent representative of rod-shaped liquid crystals, cyanobiphenyl liquid crystals have set off a wave of preparation of patterned liquid crystal organic optoelectronic devices due to their excellent electron transmission ability. These methods include printing method, nano-template method, microchannel method, etc. Although these methods can achieve very regular periodic arrangement patterns, the types of patterns prepared are limited, the microstructure of the liquid crystal is difficult to control, it is difficult to form a large area of uniform orientation, and it is difficult to transfer the dependence on the microstructure substrate, which limits the conductivity and further application of cyanobiphenyl liquid crystals. Organic small molecule materials have the advantages of fixed structure and easy adjustment, and their excellent optoelectronic properties. They are incorporated into liquid crystals, and organic small molecule donor materials are added to the electron acceptor cyanobiphenyl liquid crystal to form a cyanobiphenyl liquid crystal charge transfer complex. After the complex is oriented, the optoelectronic properties of the cyanobiphenyl liquid crystal can be greatly improved.
[0003] At present, there are few reports on the orientation methods of cyanobiphenyl liquid crystals doped with organic small molecule donor materials at home and abroad, and most of them use extremely complex orientation processes. With the help of the large surface energy difference between the superhydrophobic structured substrate and the superhydrophobic flat substrate, the directional induced assembly of the small molecule donor / cyanobiphenyl liquid crystal mixture is relatively simple and controllable, and the electrical properties of the liquid crystal composite device can be regulated; however, whether the surface tension of the solvent of the solution of the liquid crystal and the small molecule donor in the preparation process has an effect on the orientation process and the electrical properties of the final liquid crystal composite device is not involved in the prior art. Summary of the invention
[0004] The present invention aims at the deficiencies of the prior art and provides an orientation method and application of cyanobiphenyl liquid crystal doped with organic small molecule donor materials. The preparation method is simple, the pattern can be designed, and it is easy to transfer. At the same time, the influence of the solvent surface tension on the orientation and performance of the composite is studied, so as to optimize the performance of liquid crystal optoelectronic devices.
[0005] The technical solution adopted in this disclosure is:
[0006] A method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material, the method comprising the following steps:
[0007] According to the shape of the organic donor material / cyanobiphenyl liquid crystal structured pattern to be prepared, preparing a shape template of the organic donor material / cyanobiphenyl liquid crystal structured pattern;
[0008] Super-hydrophobic modification of the shape template of the organic donor material / cyanobiphenyl liquid crystal structured pattern;
[0009] Selecting and adjusting the surface tension of a solvent; using the solvent to prepare a uniform organic dispersion solution of cyanobiphenyl liquid crystal doped with an organic donor material having a certain concentration;
[0010] Selecting an upper substrate and modifying the upper substrate to be superhydrophilic;
[0011] Dropping the organic dispersion between the upper substrate and the shape template of the organic donor material / cyanobiphenyl liquid crystal structured pattern;
[0012] The organic dispersion evaporates and shrinks at a suitable temperature and is deposited on the upper substrate to form an oriented organic donor material / cyanobiphenyl liquid crystal composite structured pattern.
[0013] Optionally, the surface tension of the solvent is adjusted to be greater than 30 mN / m.
[0014] Optionally, the solvent includes dimethyl sulfoxide, N-methylpyrrolidone, chlorobenzene, or a composite solvent thereof with one or more of toluene, tetrahydrofuran, dimethylformamide, chloroform, and chloroform.
[0015] Optionally, the method further includes a peeling step, wherein the upper substrate on which the oriented organic donor material / cyanobiphenyl liquid crystal composite is deposited is peeled off from the silicon substrate to obtain a shape-controllable organic donor material / cyanobiphenyl liquid crystal composite structured pattern.
[0016] Optionally, the organic donor material comprises OXD-7 or BTBP.
[0017] Optionally, the cyanobiphenyl liquid crystal includes 8OCB, 7OCB or 9OCB.
[0018] Optionally, the mass content of the organic donor material accounts for 30%-50% of the aligned liquid crystal composite.
[0019] Optionally, the suitable temperature is 70°C-90°C.
[0020] The present invention further provides a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The cyanobiphenyl liquid crystal doped with an organic small molecule donor material is prepared according to the preparation method provided by the present invention.
[0021] The present invention further provides a fluorescent or electrical element, which comprises a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention provides a method for aligning cyanobiphenyl liquid crystals doped with an organic small molecule donor material. The alignment method is simple and low-cost.
[0024] (2) The present invention provides a method for aligning cyanobiphenyl liquid crystals doped with organic small molecule donor materials. According to different needs of practical applications, the pattern of the photolithography plate can be adjusted to change the pattern of the silicon substrate to meet the application of fluorescence or electricity.
[0025] (3) The present invention studies the process parameters in the method for preparing the orientation of cyanobiphenyl liquid crystal composites doped with organic small molecule donor materials, especially the effect of the surface tension of the solvent on the performance of the composite, provides direction for the selection of solvent, and obtains a composite with excellent electrical properties to meet application requirements.
[0026] (4) Cyanobiphenyl liquid crystal doped with organic small molecule donor materials is used as the material for optoelectronic applications. This type of material has excellent optoelectronic properties and can greatly expand the application range of liquid crystal elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 These are optical photographs, polarizing microscope photographs, polarizing microscope photographs with a light compensation plate inserted, and XRD patterns of the aligned OXD-7 / 8OCB small molecule donor / liquid crystal composite of Example 1 of the present disclosure.
[0028] Figure 2 Schematic diagram of affixing a gold film to the OXD-7 / 8OCB small molecule donor / liquid crystal composite after alignment in electrical applications in Example 1 of the present disclosure and possible molecular arrangements in the composite microwires after alignment.
[0029] Figure 3 This is a comparison chart of the current density passing through the aligned microwires of the OXD-7 / 8OCB small molecule donor / liquid crystal composite, the aligned microwires of 8OCB, and the unoriented film in Example 1 of the present disclosure.
[0030] Figure 4 Schematic diagram of the effect of different heating temperatures on the electrical properties of the OXD-7 / 8OCB small molecule donor / liquid crystal composite after alignment according to the present disclosure.
[0031] Figure 5 Schematic diagram of the electrical properties of liquid crystal composite films and micrometer wires with different small molecule OXD-7 contents disclosed in the present invention.
[0032] Figure 6 Schematic diagram of the influence of different solvents on the electrical properties of liquid crystal composite films and micrometer wires with small molecule OXD-7 content disclosed in the present invention. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0034] In order to make the purpose, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not intended to limit the present disclosure. In addition, the technical features involved in each embodiment of the present disclosure described below can be combined with each other as long as they do not conflict with each other.
[0035] Example 1
[0036] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0037] The above-mentioned composite orientation method comprises the following steps:
[0038] (1) Etching micrometer line silicon column template: The etched micrometer line silicon column template is nitrogen-doped, <100> A photoresist is applied to a 5-inch diameter, 500-micron thick silicon wafer with a crystal surface. A pre-designed chrome (Cr)-plated quartz photomask is used to irradiate the photoresist through a laser direct writing device to solidify it. After post-baking and development, the unexposed part of the silicon wafer surface is exposed. The silicon wafer with the photoresist pattern is deep-etched with a fluorine-based reagent for about 6 minutes. Finally, the substrate is debonded and cleaned with acetone and ethanol to obtain a micrometer-wire silicon column template. The micrometer-wire silicon column is 1 cm long, 2 micrometers wide, and 20 micrometers high, and the interval between the patterns is 5 micrometers.
[0039] (2) Superhydrophobic modification of micron-wire silicon pillars: Before modification, the micron-wire silicon pillar template needs to be cleaned with ethanol and acetone. The silicon pillar template is treated with a low-temperature plasma treatment apparatus (oxygen atmosphere, discharge power of 200 W, treatment time of 300 s) to activate its surface, and then placed in a vacuum oven, 5 μl of octadecyl fluorosilane is dropped, vacuum environment, temperature of 80 ° C, and left for 12 hours to obtain a micron-wire structured silicon pillar template with a superhydrophobic surface, and the water contact angle can reach about 150°.
[0040] (3) Preparation of a mixture solution of small molecule donor OXD-7 and liquid crystal 8OCB: In this embodiment, considering the influence of the solvent surface tension, chlorobenzene is first selected as the solvent, and OXD-7 and 8OCB are dispersed in chlorobenzene by ultrasound, and the concentration of the prepared solution is 2.5 mg / mL, which can range from 0.25 to 10 mg / mL. The chlorobenzene solutions of OXD-7 and 8OCB are mixed together at a volume ratio of 3:7, and a uniform solution is formed after ultrasound. At this time, the mass ratio of small molecule OXD-7 to 8OCB is 3:7.
[0041] (4) Oriented donor small molecule OXD-7 and liquid crystal 8OCB complex on SiO2@Si wafer to form a micron-line pattern: Super hydrophilic treatment of SiO2@Si wafer, using low temperature plasma treatment instrument (oxygen atmosphere, discharge power of 200W, treatment time of 300s), the treated SiO2@Si wafer becomes super hydrophilic, and the water contact angle is 0°. Take 10μl of OXD-7 / 8OCB chlorobenzene solution and drop it between the super hydrophobic micron-line silicon column template and the super hydrophilic SiO2@Si wafer to form a "sandwich" structure. The lower substrate is the super hydrophobic micron-line silicon column template, the upper substrate is the super hydrophilic SiO2@Si wafer, and the OXD-7 / 8OCB chlorobenzene solution is in the middle. After being placed in a vacuum drying oven at 80°C for 48 hours, the vacuum drying oven is closed, and the sample is taken out after the drying oven is naturally cooled to room temperature. The large surface energy difference between the silicon substrate and the super-philic leveling substrate enables the mixed homogeneous solution to form a micron-scale liquid bridge on the contact surface of the two substrates to directional induce the assembly of OXD-7 / 8OCB quantum dots. The liquid crystal 8OCB deflects under the action of the liquid bridge to form a uniform arrangement, driving the orientation of the small molecule OXD-7 and forming a charge transfer complex with the liquid crystal 8OCB. At the same time, due to the anchoring effect of the micron-line silicon substrate, a micron-line OXD-7 / 8OCB composite structure identical to the silicon substrate is formed on the upper substrate.
[0042] like Figure 1 As shown, the polarized micrographs (ae) and XRD patterns (f) of the oriented OXD-7 / 8OCB microwires; Figure 1 (a) is an optical microscopic image of micrometer wires; Figure 1 (b) and Figure 1 (c) Polarized light micrographs when the micrometer wire and the polarizer are at +45° and 0°, respectively; Figure 1 (d) Figure 1 (e) is a microscopic picture of the micrometer line and the polarizer at +45° and -45° respectively after adding the optical compensation sheet; Figure 1 (f) is the XRD pattern of the microwire.
[0043] Electrical applications of the oriented OXD-7 / 8OCB composites:
[0044] The conductive properties of the oriented OXD-7 / 8OCB composite were studied using a semiconductor parameter analyzer with a probe station. Figure 2 As shown, Figure 2 (a) is a schematic diagram of electrode arrangement: a pair of long gold electrodes are symmetrically placed on the strip-shaped OXD-7 / 8OCB complex, with a distance of about 8 microns between the electrodes. A metal probe is placed on each of the two electrodes. Figure 2 (b) is a schematic diagram of the complex structure. Figure 3 As shown, when a voltage from -100V to +100V is applied to the oriented liquid crystal composite, the current density increases by 7 orders of magnitude compared to the 8OCB composite film that has not been deflected and patterned, and the current density increases by 5 orders of magnitude compared to the oriented 8OCB microwire, which greatly improves the conductive properties of the liquid crystal.
[0045] Optionally, the micrometer wire silicon pillar template in this embodiment is a shape template for forming a cyanobiphenyl liquid crystal composite doped with an organic donor material, and a composite with a corresponding shape is prepared based on the shape template. It is understandable that the shape template of the composite can be designed according to the required circuit pattern.
[0046] Example 2
[0047] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0048] The above-mentioned composite orientation method comprises the following steps:
[0049] The orientation method and application of this embodiment are the same as those of embodiment 1, except that the heating temperature in step (4) is room temperature 25°C.
[0050] Example 3
[0051] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0052] The above-mentioned composite orientation method comprises the following steps:
[0053] The orientation method and application of this embodiment are the same as those of embodiment 1, except that the heating temperature in step (4) is 40°C.
[0054] Example 4
[0055] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0056] The above-mentioned composite orientation method comprises the following steps:
[0057] The orientation method and application of this embodiment are the same as those of embodiment 1, except that the heating temperature in step (4) is 60°C.
[0058] After studying the heating temperature, in order to achieve the orientation of the composite of the present invention, the appropriate heating temperature is between room temperature and 100°C.
[0059] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0060] The above-mentioned composite orientation method comprises the following steps:
[0061] The orientation method and application of this embodiment are the same as those of Embodiment 1, except that in step (3), the mass ratio of OXD to 8OCB is 2:8.
[0062] Example 6
[0063] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0064] The above-mentioned composite orientation method comprises the following steps:
[0065] The orientation method and application of this embodiment are the same as those of embodiment 1, except that in step (3), the mass ratio of OXD-7 to 8OCB is 4:6.
[0066] Example 7
[0067] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0068] The above-mentioned composite orientation method comprises the following steps:
[0069] The alignment method and application of this embodiment are the same as those of Embodiment 1, except that the cyanobiphenyl liquid crystal is 8OCB instead of 7OCB.
[0070] Example 8
[0071] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0072] The above-mentioned composite orientation method comprises the following steps:
[0073] The alignment method and application of this embodiment are the same as those of Embodiment 1, except that the cyanobiphenyl liquid crystal is 8OCB instead of 9OCB.
[0074] The electrical properties of the cyanobiphenyl liquid crystal doped with the small molecule donor material of the present invention after orientation were studied. When the concentration of the OXD-7 / 8OCB mixed organic solution was fixed at 2.5 mg / mL, the heating temperature in step (4) during the preparation process had a significant impact on the conductive properties of the prepared liquid crystal composite microwires. Figure 4 As shown, Figure 4 (a) is the JV curve of liquid crystal composite microwire; Figure 4 (b) is the relationship between the current density value of each liquid crystal composite microwire and the heating temperature during the alignment process when a voltage of -60 V is applied; Figure 4 (c) is the XRD spectrum. Figure 4 As shown in Figure 1, when the heating temperature is 70℃-90℃, the current density passing through the microwire increases by 3 orders of magnitude compared to the current density when heated at other temperatures. In particular, when the heating temperature is 80℃, the current density increases by 5 orders of magnitude. Subsequently, the XRD method was used to study the liquid crystal properties of the microwires formed at different heating temperatures, and the results are as follows: Figure 4 (c) XRD spectrum shown. When the heating temperature is 70℃-90℃, the XRD curve shows a strong diffraction peak at 3.7°, which corresponds to the (001) plane of 8OCB, indicating that the liquid crystal molecules form a layered and ordered arrangement of the smectic phase, and the 8OCB molecules stand vertically on the upper substrate. The diffraction peak at 6.9° comes from the (200) plane of the small molecule OXD-7, indicating that OXD-7 presents a B6 phase arrangement. At 80℃, the liquid crystal and small molecules are uniformly arranged to form a good electron donor-acceptor pairing, so the conductivity of the sample is the strongest at this time. When the heating temperature is lower than 70℃ (25℃-60℃), only a strong diffraction peak of 8OCB at 3.7° is observed, indicating that low temperature is conducive to the orientation of liquid crystal 8OCB. When the temperature is higher than 90℃ (100℃), the small molecule OXD-7 shows a strong diffraction peak, while the diffraction peak of 8OCB is significantly weakened, indicating that high temperature is conducive to the uniform arrangement of OXD-7, while the orientation of 8OCB becomes very weak. Correspondingly, when the heating temperature is lower than 70℃ or higher than 90℃, the current density of the sample is significantly lower than 70℃-90℃. Only when 8OCB and OXD-7 form a uniform arrangement at the same time can the conductivity in the sample reach the maximum. The uniform arrangement of a single 8OCB or OXD-7 has little effect on the conductivity of the liquid crystal composite.
[0075] like Figure 5As shown, the effect of the mass content of small molecule OXD-7 on the conductive properties of the prepared liquid crystal composite microwires was studied, wherein the concentration of the OXD-7 / 8OCB organic mixed solution was fixed at 2.5 mg / mL and the heating temperature during the orientation process was 80°C. Figure 5 (a) JV curves of liquid crystal composite films and micrometer wires with different OXD-7 contents; Figure 5 (b) is a comparative bar graph of the current density passing through the OXD-7 / 8OCB unoriented film, the 8OCB unoriented film and the oriented microwires, and the liquid crystal composite microwires with OXD-7 contents of 30%, 40%, and 50% when a voltage of -60 V is applied;
[0076] Figure 5 (c) is the relationship between the current density value of each composite liquid crystal microwire and the OXD-7 content when a voltage of -60 V is applied; Figure 5 (d) is the XRD spectrum. As can be seen from the figure, when the mass content of OXD-7 is 30%-50%, the current density passing through the microwires with other contents is increased by 3 orders of magnitude, especially when the OXD-7 content is 30%, it is increased by nearly 5 orders of magnitude, greatly improving the conductivity of OXD-7 / 8OCB. The corresponding XRD diffraction spectrum shows a strong diffraction peak at 3.7°, which corresponds to the (001) plane of 8OCB, indicating that the liquid crystal molecules form a layered and orderly arrangement of the smectic phase, and 8OCB stands vertically on the upper substrate. The diffraction peak at 6.9° comes from the (200) plane of the small molecule OXD-7, indicating that OXD-7 presents a B6 phase arrangement. When the OXD-7 content is 30%, the liquid crystal and small molecules are uniformly arranged to form a good electron donor-acceptor pairing. At this time, the conductivity of the composite microwire is the strongest. When the content of OXD-7 is lower than 30%, the XRD diffraction spectrum has three peaks, a diffraction peak appears near 3.0°, corresponding to the trans-dimer smectic phase (partialbilayersmectic Ad, SmAd) of 8OCB, a diffraction peak appears at 3.7°, corresponding to the diffraction peak of the (001) plane of the layered smectic phase of 8OCB, and the third peak appears at 6.9°, corresponding to the B6 phase of the small molecule OXD-7. The SmAd arrangement of 8OCB is not conducive to the formation of a donor-acceptor complex in the composite microwire, so the conductivity is greatly reduced. When the content of OXD-7 is higher than 50%, only the diffraction peak of the B6 phase of OXD-7 appears, and the diffraction peak of 8OCB does not appear, indicating that 8OCB has not formed an ordered arrangement and the conductivity is not high.
[0077] Example 9
[0078] This embodiment considers the influence of the surface tension of the solvent on the performance of the final device during the preparation of the cyanobiphenyl liquid crystal composite doped with an organic donor material.
[0079] The invention discloses an orientation method of a cyanobiphenyl liquid crystal composite doped with an organic small molecule donor material. The organic small molecule donor in the composite structure is OXD-7, and the cyanobiphenyl liquid crystal is 8OCB.
[0080] The above-mentioned composite orientation method comprises the following steps:
[0081] According to the orientation method of Example 1, the organic solvent chlorobenzene in step (3) is replaced by toluene, tetrahydrofuran, dimethylformamide, chloroform, chloroform, and n-hexane, respectively. This experiment confirms that chlorobenzene, toluene, tetrahydrofuran, dimethylformamide, chloroform, and chloroform can all allow the composite to achieve excellent orientation. When the solvent is replaced with n-hexane, the conductivity of the microwire decreases, indicating that the surface tension of the solvent has an effect on the orientation and conductivity of the microwire; the surface tension values of chlorobenzene, toluene, tetrahydrofuran, dimethylformamide, chloroform, and chloroform are 33mN / m, 28mN / m, 26.4mN / m, dimethylformamide 25.7mN / m, chloroform 28.9mN / m, and chloroform 27.6mN / m, respectively; when the surface tensions of these solvents are all greater than 25mN / m, the composite microwire can achieve excellent orientation ( Figure 6 ). The surface tension of n-hexane is 18.92 mN / m. When this solvent is used, the orientation of the microwires decreases.
[0082] In order to further study the effect of solvent surface tension, N-methylpyrrolidone (NMP) (surface tension of about 34 mN / m) and dimethyl sulfoxide (DMSO) (surface tension of about 42.3 mN / m) were selected as solvents. The test results are shown in Figure 2. Figure 6 shown.
[0083] It can be seen that the performance of the microwires obtained with solvents with high surface tension is better, and the current density of the oriented composite microwires with dimethyl sulfoxide as the solvent has increased by at least 10 times, that is, the adjustment of the solvent surface tension can affect the assembly process of liquid crystal molecules and small molecule donors, thereby affecting the orientation and electrical properties of the composite.
[0084] In addition, in order to obtain any desired surface tension, or to combine the advantages and disadvantages of various solvents (for example, some solvents are highly toxic, and some solvents are expensive), some solvents can be compounded, such as dimethyl sulfoxide (DMSO) and chlorobenzene can be compounded and mixed in a certain proportion. The surface tension of the mixed solvent can be measured according to the hanging drop method.
[0085] Specifically, solvents with high surface tension, such as chlorobenzene, toluene, tetrahydrofuran, dimethylformamide, chloroform, chloroform, etc., usually have surface tension values greater than 25mN / m. More preferably, solvents with surface tension values greater than 33, such as N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), or a compound solvent of dimethyl sulfoxide and other solvents (such as chlorobenzene, toluene, tetrahydrofuran, dimethylformamide, chloroform, chloroform); it is more conducive to forming a stable liquid bridge and promoting the directional arrangement of liquid crystal molecules and donor small molecules in the liquid bridge. When the solvent evaporates, the contraction force of the liquid bridge can more effectively drive the molecular orientation and form a more ordered structure, thereby enhancing the conductivity of the device. In contrast, solvents with low surface tension (such as n-hexane, whose surface tension value is 18.92mN / m) may cause the liquid bridge to be unstable, making it difficult to form an effective orientation force, making the structure of the composite disordered, and reducing the conductivity.
[0086] In practical applications, most surfactants are for reducing the surface tension of solvents. In the application scenario of the present invention, increasing the surface tension of the solvent is conducive to the orientation of the cyanobiphenyl liquid crystal complex. Therefore, in the whole scheme, when configuring the solution of liquid crystal and small molecule donor, considering the influence of the solvent surface tension, screening the solvent and consciously adjusting the surface tension are important steps to improve the efficiency and performance of the complex orientation. However, the choice of solvent should also consider its solubility, stability and compatibility with subsequent processes (such as evaporation and drying process) to liquid crystal and small molecule donors. Therefore, although the surface tension of some solvents is higher, whether it is suitable for the implementation of the present invention, it is necessary to verify its specific performance in the process of preparing the complex by experiments.
[0087] Compared with the prior art, the present invention has the following advantages:
[0088] (1) The present invention provides a method for aligning cyanobiphenyl liquid crystals doped with small molecule donor materials. The alignment method is simple and low-cost.
[0089] (2) The present invention provides a method for aligning cyanobiphenyl liquid crystals doped with small molecule donor materials. According to different needs of practical applications, the pattern of the photolithography plate can be adjusted to change the pattern of the silicon substrate to meet the application of fluorescence or electricity.
[0090] (3) The present invention studies the process parameters in the method for preparing the orientation of cyanobiphenyl liquid crystal composites doped with organic small molecule donor materials, especially the effect of the surface tension of the solvent on the performance of the composite, provides direction for the selection of solvent, and obtains a composite with excellent electrical properties to meet application requirements.
[0091] (4) Cyanobiphenyl liquid crystal doped with small molecule donor materials is used as the material for optoelectronic applications. This type of material has excellent optoelectronic properties and can greatly expand the application range of liquid crystal elements.
[0092] The above-described embodiments are only descriptions of the preferred implementation methods of the present disclosure, and the preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Without departing from the design spirit of the present disclosure, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present disclosure should fall within the protection scope determined by the claims of the present disclosure.
Claims
1. A method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material, characterized in that: The orientation method comprises the following steps: According to the shape of the organic donor material / cyanobiphenyl liquid crystal structured pattern to be prepared, preparing a shape template of the organic donor material / cyanobiphenyl liquid crystal structured pattern; Super-hydrophobic modification of the shape template of the organic donor material / cyanobiphenyl liquid crystal structured pattern; Selecting and adjusting the surface tension of a solvent; using the solvent to prepare a uniform organic dispersion solution of cyanobiphenyl liquid crystal doped with an organic donor material having a certain concentration; Selecting an upper substrate and modifying the upper substrate to be superhydrophilic; Dropping the organic dispersion between the upper substrate and the shape template of the organic donor material / cyanobiphenyl liquid crystal structured pattern; The organic dispersion evaporates and shrinks at a suitable temperature and is deposited on the upper substrate to form an oriented organic donor material / cyanobiphenyl liquid crystal composite structured pattern.
2. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 1, characterized in that: The surface tension of the solvent is adjusted to be greater than 30 mN / m.
3. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 2, characterized in that: The solvent includes dimethyl sulfoxide, N-methylpyrrolidone, chlorobenzene or a composite solvent of dimethyl sulfoxide, N-methylpyrrolidone, chlorobenzene and one or more of toluene, tetrahydrofuran, dimethylformamide, chloroform and chloroform.
4. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 1, characterized in that: The method also includes a peeling step of peeling the upper substrate on which the oriented deposited organic donor material / cyanobiphenyl liquid crystal complex is deposited from the silicon substrate to obtain a shape-controllable organic donor material / cyanobiphenyl liquid crystal complex structured pattern.
5. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 1 or 2, characterized in that: The organic donor material includes OXD-7 or BTBP.
6. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 1 or 2, characterized in that: The cyanobiphenyl liquid crystal includes 8OCB, 7OCB or 9OCB.
7. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 1 or 2, characterized in that: The mass content of the organic donor material accounts for 30%-50% of the liquid crystal composite after alignment.
8. The method for aligning a cyanobiphenyl liquid crystal composite doped with an organic donor material according to claim 1 or 2, characterized in that: The suitable temperature is 70°C-90°C.
9. An oriented cyanobiphenyl liquid crystal composite doped with a donor material, characterized in that: The cyanobiphenyl liquid crystal doped with an organic donor material is prepared according to the method according to any one of claims 1-8.
10. A fluorescent or electrical element, characterized in that: The fluorescent or electrical element comprises the aligned cyanobiphenyl liquid crystal composite doped with an organic donor material as claimed in claim 9.
Citation Information
Patent Citations
Low-voltage liquid crystal composition and low-voltage polymer dispersion liquid crystal material
CN106479516A
Method for controlling liquid crystal molecular orientation through special rod-shaped molecules or polymer thereof
CN108485682A
Fullerene-doped nematic liquid crystal complex with high-speed electrooptic response and liquid crystal device based on it
US20070262287A1
Detection of vapor phase compounds by changes in physical properties of a liquid crystal
US20100093096A1
Optically anisotopic film, process for producing optically anisotopic film, substrate for liquid crystal cell, and liquid crystal display device
US20110117295A1